2021
DOI: 10.3390/antiox10020307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of a Rosmarinic Acid-Enriched Fraction Prepared from Nga-Mon (Perilla frutescens) Seed Meal on Osteoclastogenesis through the RANK Signaling Pathway

Abstract: The aim of this study is to determine antioxidant and anti-inflammatory activities relating to the antiosteoporosis effects of various perilla seed meal (PSM) fractions. The remaining waste of perilla seed obtained from cold oil compression was extracted with 70% ethanol and sequentially fractionated according to solvent polarity with hexane, dichloromethane, ethyl acetate, and water. The results indicated that the seed-meal ethyl acetate fraction (SMEF) exhibited the highest antioxidant and anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 77 publications
4
27
0
Order By: Relevance
“…Our results also demonstrated that RA-RF, a natural polyphenol component found in perilla, reduced IL-6, IL-8, TNF-α, and COX-2 gene expression. This finding is in agreement with our previous report showing that RA extracted from perilla reduced mRNA levels of pro-inflammatory cytokines [20,22,74]. Additionally, RA-rich extract from Trichodesma khasianum leaves could diminish ROS production and inflammatory modulators such as IL-6, TNF-α, and COX-2 levels in vitro and in vivo [75].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results also demonstrated that RA-RF, a natural polyphenol component found in perilla, reduced IL-6, IL-8, TNF-α, and COX-2 gene expression. This finding is in agreement with our previous report showing that RA extracted from perilla reduced mRNA levels of pro-inflammatory cytokines [20,22,74]. Additionally, RA-rich extract from Trichodesma khasianum leaves could diminish ROS production and inflammatory modulators such as IL-6, TNF-α, and COX-2 levels in vitro and in vivo [75].…”
Section: Discussionsupporting
confidence: 93%
“…This work resembles previous studies showing that the ethanolic extract of perilla leaves disrupted c-Jun phosphorylation [93]. Moreover, RA-rich extract from perilla seed meal could reduce RANKL-induced c-Jun translocation in RAW macrophage cells [74]. In addition, RA alone exerted protective effects against oxidative stress, inflammation, invasion, migration, and MMP-9 protein expression through the AP-1 signaling cascade [94,95].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are consistent with those reported previously. It was found that cold-pressed PSO mainly consisting of ω-3 fatty acid reduced the ROS production induced by ultraviolet radiation in normal human dermal fibroblasts [53], and the EA fraction from PSM, which contained high quantities of RA, inhibited ROS production in RANKL-induced RAW 264.7 cells [54]. Our results suggest that both PSO and RA-RF have antioxidant ability and equally inhibit ROS generation.…”
Section: Discussionmentioning
confidence: 53%
“…The inhibition of intracellular ROS production induced by hydrogen peroxide (H 2 O 2 ) was determined following the method of Saenjum et al [21] and Phromnoi et al [22] with slight modifications. The assay measures the oxidation of 2 ,7 -dichlorodihydrofluorescein diacetate (H 2 DCF-DA) to fluorescent 2 ,7 -dichlorofluorescein (DCF).…”
Section: Inhibition Of Induced Intracellular Ros Productionmentioning
confidence: 99%